2010
DOI: 10.1128/mcb.01067-09
|View full text |Cite
|
Sign up to set email alerts
|

Rab13 Regulates Neurite Outgrowth in PC12 Cells through Its Effector Protein, JRAB/MICAL-L2

Abstract: Neurite outgrowth is the first step in the processes of neuronal differentiation and regeneration and leads to synaptic polarization and plasticity. Rab13 small G protein shows an increased mRNA expression level during neuronal regeneration; it is therefore thought to be involved in this process. We previously identified JRAB ( Neuronal cells are symmetrically shaped in the very early stages of development. When fully developed, they are asymmetrical, with one long thin axon. The polarization of cell morpholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
85
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 26 publications
2
85
0
1
Order By: Relevance
“…Rab13, a Rab closely related to Rab8 and Rab10, is reported to be necessary for neurite elongation (Sakane et al, 2010). Additionally, Rab17 and Rab22, which belong to different subfamilies of Rab8, have been reported to be necessary for dendrite (Mori et al, 2012) and neurite elongation (Wang et al, 2011a), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Rab13, a Rab closely related to Rab8 and Rab10, is reported to be necessary for neurite elongation (Sakane et al, 2010). Additionally, Rab17 and Rab22, which belong to different subfamilies of Rab8, have been reported to be necessary for dendrite (Mori et al, 2012) and neurite elongation (Wang et al, 2011a), respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that some bMERB domain containing effector proteins form an auto-inhibited state in which the bMERB domain binds to the actin-binding CH-domain and inhibit its interaction with actin. Thus, bMERB domains might contain one Rab-binding site for recruitment and one for release of the auto-inhibition (Schmidt et al, 2008;Sakane et al, 2010;Sun et al, 2016). It is also possible that the domains might simultaneously bind two different Rabs and act as sorting hubs in endosomal trafficking.…”
Section: Bivalent Monomeric Rab Effectors (Bmerbs; Bivalent Mical/ehmentioning
confidence: 99%
“…Consistently, filamin levels also correlate with invasiveness of melanoma cell lines, and high filamin levels are predictive of poor prognosis in melanoma patients (77). Interestingly, in the absence of Rab13, MICAL-L2 and actinin-4 promote cell-cell adhesion by stimulating thick actin bundling at the cell periphery (44,45). Consistently, high levels of actinin-4 are associated with decreased cell motility (78,79).…”
Section: Cell Migration and Scatteringmentioning
confidence: 55%
“…Insulin stimulation increases the pool of active Rab13, which binds to the Rab13 effector MICAL-L2, relieving MICAL-L2 auto-inhibition and thus allowing MICAL-L2 to recruit various actin regulatory proteins including actinin-4 ( Fig. 2) (5,44,45). A complex involving Rab13, MICAL-L2, and actinin-4 binds to GLUT4 in an insulindependent manner, allowing docking/tethering of GLUT4 vesicles at the cell surface and thus enabling their fusion (46).…”
Section: Cell Metabolismmentioning
confidence: 99%